The role of CEOs in managing corporate reputation through communication leadership among the leading media government-linked companies - Md Tahir, Zainal Arifin; Abdullah, Zulhamri; Syed Alsagoff, Syed Agil; Hasan, Nurul Aien (2018)
This paper forwards as a proposal to conduct a study that will explore and examine the role of CEOs as communication leaders among the leading media government-linked companies. All the other C-level executives who will be later identified as part of the top-level corporate communication team will be included. Their collective narratives are expected to yield ideas concerning how their respective corporate communication schemes are structured, managed and practiced. The main research question is: how does the role of the CEO influence or mediate in the relationship between communication leadership and corporate reputation strategies? By addressing this main question, new forms of knowledge can be derived. The most crucial among which is how the leading media government-linked companies are utilizing their media resources and C-level talents to promote corporate reputation. This of course is in view of their high vulnerability to strong institutional/political pressures. A qualitative research method is proposed because thick narrative data are needed in order to capture a robust understanding on C-level practices of reputation management through communication. Data collection will be made through face-to-face in-depth interviews. The voice-recorded interviews will be replayed, transcribed, organized and will undergo thematic analysis for pattern detection and theme generation. The main theory that will be used to interpret the findings and guide the analysis is institutional theory. This theory is pertinent in view of the structural preconditions that govern and give the leading media government-linked companies their legitimacy. A precedent study has used neo-institutional theories in explaining the interactions involved between the media, society and organizations in relation to CEO communication and positioning. After academic validation, the study aspires to make a significant contribution to the study of communication leadership. At this writing the amount of literature available on communication leadership in the context of Malaysian leading media government linked companies is relatively scant.